2013
DOI: 10.5688/ajpe7719
|View full text |Cite
|
Sign up to set email alerts
|

Use and Views on Social Networking Sites of Pharmacy Students in the United Kingdom

Abstract: Objective. To investigate students' use and views on social networking sites and assess differences in attitudes between genders and years in the program. Methods. All pharmacy undergraduate students were invited via e-mail to complete an electronic questionnaire consisting of 21 questions relating to social networking. Results. Most (91.8%) of the 377 respondents reported using social networking Web sites, with 98.6% using Facebook and 33.7% using Twitter. Female students were more likely than male students t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 12 publications
9
63
0
1
Order By: Relevance
“…Comparing with this result, most pharmacy students (83.8%) in the United Kingdom responded that they invested less than 2 hours to use SNSs although a small percentage of the students (2.3%) spent more than 3 hours per day on SNSs. 12 These results may suggest that using SNSs plays an important role in keeping relations between participants in daily lives. One of the interesting findings from this study is that 40.5% of Korean pharmacy students indicated that a pharmacy employer should not consider a prospective employee's SNS profile in making a hiring decision.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Comparing with this result, most pharmacy students (83.8%) in the United Kingdom responded that they invested less than 2 hours to use SNSs although a small percentage of the students (2.3%) spent more than 3 hours per day on SNSs. 12 These results may suggest that using SNSs plays an important role in keeping relations between participants in daily lives. One of the interesting findings from this study is that 40.5% of Korean pharmacy students indicated that a pharmacy employer should not consider a prospective employee's SNS profile in making a hiring decision.…”
Section: Discussionmentioning
confidence: 89%
“…Approximately 70% of students had Facebook profiles, but the percentage of Korean pharmacy students with Facebook profiles is lower than those reported for pharmacy students in the United States and the United Kingdom. 6,12 This may be because more than 90% of Korean's smartphone users have Kakaotalk profiles and this is overwhelmingly the No. 1 SNS used by Korean people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using patient confidentiality in various postings 17 and writing disrespectful comments about colleagues and employers. 18,19 For instance, in a sample of 880 medical students in Australia, 20 34% reported to having unprofessional content in their social media accounts, for example, evidence of being intoxicated (34.2%), illegal drug use (1.6%), posting patient information (1.6%), and depictions of an illegal act (1.1.%). Unsurprisingly, many professional bodies have developed social media guidelines for its registrants in order to clearly delineate the professional responsibilities and expectations regarding social media behaviour by healthcare professionals.…”
Section: Methodsmentioning
confidence: 99%